An efficiency analysis of the selected enterprises in the Mekong river delta, Viet Nam : - Quan, Minh Nhut (Trường Đại học Cần Thơ, 2008)
This study aims: To characterize enterprises in the Mekong Delta; To measure efficiency of the selected enterprises by using the Data Envenlopment Analysis (DES). Determining and comparing efficiency distributions of the selected enterprises in the MD;...